Ground motion duration effects on nonlinear seismic response. - Iervolino, Iunio (Earthquake engineering & structural dynamics.)
The study presented in this paper addresses the question of which nonlinear demand measures are sensitive to ground motion duration by statistical analyses of several case studies. A number of single degree of freedom (SDOF) structures were selected considering: (1) four oscillation periods; (2) three evolutionary and non-evolutionary hysteretic behaviours; (3) two target ductility levels. Effects of duration are investigated, by nonlinear dynamic analysis, with respect to six different demand indices ranging from displacement ductility ratio to equivalent number of cycles. Input is made of six real accelerogram sets representing three specific duration scenarios (small, moderate and large duration). For all considered demand quantities time-history results are formally compared by statistical hypothesis test to asses the difference, if any, in the demand concerning different scenarios. Incremental dynamic analysis curves are used to evaluate duration effect as function of ground motion intensity (e.g. spectral acceleration corresponding to the SDOF's oscillation period). Duration impact on structural failure probability is evaluated by fragility curves. The results lead to the conclusion that duration content of ground motion is statistically insignificant to displacement ductility and cyclic ductility demand. The conclusions hold regardless of SDOF's period and hysteretic relationship investigated.